Interview with Victor Nee: “Sociologists Always Want to Reinvent the Conceptual Map and to Come up with the New Conceptual Scheme that Identifies Something as Important” (Part 1) - Victor Nee (Journal of Economic Sociology, 2014)
Victor Nee was interviewed by Alexander Kurakin, Senior Lecturer at the Higher School of Economics. This interview was conducted during the international conference “Embeddedness and Beyond: Do Sociological Theories Meet Economic Realities?” (Moscow, 25–28 October 2012), at which Prof. Nee co-chaired the mini-conference “Organizations and Institutions in Emerging Markets.”Prof. Nee emphasizes that economic sociology cannot be built only on the argument that networks matter. While important, this sole focus does not allow economic sociology to progress to the societal level. For that, economic sociology needs to incorporate institutional structures — both formal and informal — into its analysis, as it extends the sociological perspective to the study of economic behavior. Prof. Nee also discusses his recent book “Capitalism from Below” (co-authored with S. Opper, 2012), which puts into practice and explains through such multi-dimensional institutional analysis how private-enterprise capitalism emerged in China.In this issue the journal presents the first part of the interview. The second part will be published in May 2014.